MOBILITAS PEKERJAAN DARI NELAYAN KE NON NELAYAN DI DESA / KELURAHAN BAGAN HULU KECAMATAN BANGKO KABUPATEN ROKAN HILIR - Ummi Fadilla Latifah; Indrawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The background of this research was from writer’s observation of the occupational mobility of fishing to non fishing in Bagan Hulu, Bangko district, Rokan Hilir regency. The formulations of problems are what factors influence the mobility and what are the forms of its mobility. The population of this research was people who used to work as a traditional fisherman and of course they have experienced the mobility themselves. By using census technique, the samples were obtained by taking the entire population in Bagan Hulu of 20 people (as correspondents). While the data was collected through observations, interviews and literature reviews. Analysis of the data used is descriptive and quantitative methods.The result of the research shows that among these 20 correspondents , they changed their occupation as a seller in the market, a farmer for rental paddy field or their own field, a contactor for builds many things and odd jobs (whatever jobs they could handle). This kind of mobility happened because of many things, one of them is economic factors. Not all of them experienced the progress in a good way except for 80 % of them. The progresses are the changing of their daily life in the form of income, family welfare, infrastructure and etc. In other word, it could be said that this 80% correspondents are having vertical mobility upward. For the rest could be said that they are having vertical mobility downward and horizontal mobility.Keywords: Occupational Mobility, Bagan Hulu’s Traditional Fishing.